ТУРИЗМ ЯК КРОСКУЛЬТУРНА РЕАЛЬНІСТЬ У СУЧАСНОМУ ОСВІТНЬОМУ ПРОСТОРІ (Педагогіка вищої та середньої школи, 2004)
The problems of vocational pedagogies, і e., tourism pedagogics are being dealt with in the frame of tourism logy. The basis categories are separated.